Awareness women of childbearing age on early detection cervical cancer: a scoping review - Siti Rukmana; Dewi Rokhanawati; Nurul Kurniati (International Journal of Health Science and Technology, 2021)
Cervical cancer is caused by HPV acquired by sexual intercourse. Women know that screening is done to detect cervical cancer early. The purpose of this review is to determine the awareness of early detection of cervical cancer in women of childbearing age. Scoping Review by Arksey and O'Malley. Date based are Wiley, Pubmed, Proquest and EBSCO. 9 articles were reviewed by  JBI. The results revealed  the factors that influence women for  early detection types of cervical cancer form of knowledges and education, good knowledge can generate women's awareness of early detection, health promotion and socialization from healthcare proffessionals is very influential.